2021
DOI: 10.7554/elife.70557
|View full text |Cite
|
Sign up to set email alerts
|

3′HS1 CTCF binding site in human β-globin locus regulates fetal hemoglobin expression

Abstract: Mutations in the adult β-globin gene can lead to a variety of hemoglobinopathies, including sickle cell disease and β-thalassemia. An increase in fetal hemoglobin expression throughout adulthood, a condition named Hereditary Persistence of Fetal Hemoglobin (HPFH), has been found to ameliorate hemoglobinopathies. Deletional HPFH occurs through the excision of a significant portion of the 3' end of the β-globin locus, including a CTCF binding site termed 3'HS1. Here, we show that the deletion of this CTCF site a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…These data indicate that the Townes strain lacks key cis -regulatory elements for controlling human β-globin switching, which could include the long non-coding RNA locus, BGLT3 , the globin pseudogene HBBP1 and the 3′ HS1 downstream of HBB ( Fig. 2 B) ( Himadewi et al, 2021 ; Huang et al, 2017 ; Ivaldi et al, 2018 ). Efforts to model SCD in mice harboring the β-globin YAC have been complicated by excessive perinatal death, most likely because the human γ-to-β-globin gene switch occurs during mid-gestation in mice, thereby eliminating the protective effects of HbF expression during birth-associated hypoxic trauma ( Chang et al, 1998 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These data indicate that the Townes strain lacks key cis -regulatory elements for controlling human β-globin switching, which could include the long non-coding RNA locus, BGLT3 , the globin pseudogene HBBP1 and the 3′ HS1 downstream of HBB ( Fig. 2 B) ( Himadewi et al, 2021 ; Huang et al, 2017 ; Ivaldi et al, 2018 ). Efforts to model SCD in mice harboring the β-globin YAC have been complicated by excessive perinatal death, most likely because the human γ-to-β-globin gene switch occurs during mid-gestation in mice, thereby eliminating the protective effects of HbF expression during birth-associated hypoxic trauma ( Chang et al, 1998 ).…”
Section: Discussionmentioning
confidence: 94%
“…The absence of these elements in the Townes strain may impair expression of the HBG1 transgene. In this regard, the HBBP1 and BGLT3 genes ( Huang et al, 2017 ; Ivaldi et al, 2018 ) and 3′ HS1, a CTCF-binding region downstream of HBB ( Himadewi et al, 2021 ), have been shown to regulate γ-globin gene expression, contain human-specific ATAC-seq peaks and are not present in the Townes strain.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Chromatin immunoprecipitation was performed using a previously described protocol ( 53 ). Briefly, 1 million cells were fixed with 1% formaldehyde and sonicated with Covaris E220 or Bioruptor Plus.…”
Section: Methodsmentioning
confidence: 99%
“…mRNA-seq was performed as previously described ( 53 ). Total RNA from OCI-AML3 cells treated with DMSO, dTAG-13, and selinexor (ApexBio, B1464) with specific doses and time was isolated using the Qiagen RNeasy RNA isolation kit (micro).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation